Larval shell morphology of Inoceramus pictus: all suspicions confirmed - Ifrim, Christina (Paläontologische Zeitschrift, 2017)
Inoceramids were eurytopic bivalves and have a wide application as biostratigraphic index fossils in the Upper Cretaceous. Their paleoecology, however, is far from being understood. Here the prodissoconch of Inoceramus pictus is described. It was found in an upper Cenomanian shallow water methane-seep deposit in the Tropic Shale, southern Utah, USA. The larval shell consists of a small prodissoconch-1 and a large prodissoconch-2. The shell morphology indicates a planktotrophic larval phase with wide dispersal potential, and which confirms previous hypotheses of inoceramid larval ecology. Comparison with other inoceramid prodissoconchs shows that larval shell morphology cannot generally explain dispersal, and that more factors must have played a role in the distribution of species.